AutoCAD 2005 and AutoCAD LT 2005 bible - Finkelstein, Ellen (Wiley Pub., 2004)
If you have invested in AutoCAD 2005 or AutoCAD LT 2005, you want to get the most from these top quality tools. This comprehensive guidebook gives you a ready reference on every detail of both products. The Chapter 1 tutorial gets you going immediately, and the early chapters provide a thorough education in drawing basics. From there, you’ll examine layers, text, dimensions, 2D and 3D coordinates, 3D modeling, rendering, customizing the program, and everything else you need to know. Inside, you'll find complete coverage of AutoCAD 2005 and AutoCAD LT 2005: Draw and edit 2D and 3D objects, including tables, text, and dimensions, use layers, colors, and linetypes, and print (or plot); Work with blocks, reference other drawings, and connect to external databases; Manage drawing data using tool palettes, fields, and drawing sets, integrate other applications, and post your work on the Web; Create scripts, custom linetypes and hatch patterns, shapes, fonts, and custom menus; Program AutoCAD with AutoLISP® and VBA.